2005
DOI: 10.1007/s00127-005-0985-x
|View full text |Cite
|
Sign up to set email alerts
|

Public opinions and beliefs about the treatment of depression in urban Turkey

Abstract: The beliefs that "psychological and social interventions are more effective than pharmacotherapy" and "antidepressants are harmful and addictive" must specifically be taken into account in clinical practice and in anti-stigma campaigns. Additional studies are needed to understand the public's tendency to conceptualise depression as a psychosocial problem. In clinical practice, depression should be introduced as a bio-psychosocial disease whatever its cause: biological, psychological or social. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
6
32
0
3
Order By: Relevance
“…The qualitative descriptions enrich the findings from the survey data by illustrating how patient-level characteristics influence views on antidepressants. Our study confirms and builds upon aspects of other studies investigating patient attitudes toward depression care and acceptability of depression treatment (Cooper et al, 2003; Ozmen et al, 2005). However, our study elicited themes from older patients instead of utilizing survey data measuring fixed choice responses of attitudes toward antidepressants thereby allowing us to relate the insider perspective directly to the reported use of antidepressants which had been only partially explained by patient-level characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…The qualitative descriptions enrich the findings from the survey data by illustrating how patient-level characteristics influence views on antidepressants. Our study confirms and builds upon aspects of other studies investigating patient attitudes toward depression care and acceptability of depression treatment (Cooper et al, 2003; Ozmen et al, 2005). However, our study elicited themes from older patients instead of utilizing survey data measuring fixed choice responses of attitudes toward antidepressants thereby allowing us to relate the insider perspective directly to the reported use of antidepressants which had been only partially explained by patient-level characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…As to pharmacological therapy, fear of addictive effects is reported as the main cause for concern, in line with a Turkish study [36]. According to respondents, depression is better cured with vitamins (seen as free from side effects) than with potentially harmful antidepressants.…”
Section: Discussionsupporting
confidence: 52%
“…Much research on depression, anxiety, and somatic symptoms has been conducted in Turkey (e.g., Akdemir et al, 2001;Kara, Yazici, Gu¨lec¸, & Ü nsal, 2000;Ö zmen et al, 2005;Sayar et al, 2000;Sayar, Kirmayer, & Taillefer, 2003;Tu¨rkc¸apar, Ö zyurt, M. F., Ö rsel, S., & Tu¨rkc¸apar, 2005). These studies have found that anger attacks are highly prevalent (49%) in depressed Turkish patients (Sayar et al, 2000), that depressive disorder is often accompanied by anxiety disorders, and that somatic symptoms may be more closely related to the level of anxiety than to depressive symptoms as such (Sayar et al, 2003).…”
Section: Borra 663mentioning
confidence: 96%